Determination of Safe Benzene Concentration in Tank Car Crew at PT Pertamina Patria Niaga (Indian Journal of Forensic Medicine & Toxicology, 2020)
Benzene is a compound that can cause carcinogenic effects in humans. The purpose of this study was to determine the level of health risk due to exposure to benzene through inhalation on tank car crews at Pertamina Patra Niaga. This type of research is a descriptive, observational and cross sectional study. The population in this study were all the Tank Car Crew (AMT) who worked in Pertamina Patra Niaga, amounting to 8 people. The sampling technique is the total population, so the sample is 8 workers. Data analysis used quantitative data to determine the safe concentration of (C) benzene in workers from animal body weight of white rats (W animals), body surface of experimental animals (BSA animals), body weight (W), height of workers (h), worker body surface area (BSA), worker respiratory rate (BR), working time (t), benzene (C) concentration, animal km. Human km, NOAEL and safe dose toxin limit (SHD).The results showed measurements of benzene concentration at PT. Pertamina Patra Niaga is 0.26 mg / m3 (0.08 ppm), which means the concentration of benzene is still below the Threshold Value (NAB) according to Minister of Manpower Regulation No. 13 / MEN / X / 2011 at 0.5 ppm. Based on the calculations that have been done, the safe limit value is 0.02 ppm. This value if according to the Minimum Risk Level (MRL) of 2007 ATSDR exceeds that which is set at 0.009 ppm daily for acute effects and 0.003 ppm daily for chronic effects, so that control efforts are needed to be protected from the adverse effects of benzene on the health of workers. Control recommendations are to consume CYP2E1 enzyme contained in beef liver and salmon which serves to reduce benzene levels in the body, use Personal Protective Equipment (PPE) in the form of mask respirators and plant a number of ornamental plants that can absorb and reduce benzene concentrations such as Boston and Golden Photos1
Keywords: Benzene, safe concentration, workers of PT Pertamina Petra Niaga